2001
DOI: 10.1300/j144v04n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Crop Allelopathy and Its Role in Ecological Agriculture

Abstract: A number of crops exhibit allelopathic interactions that play a significant role in the complex environment of agroecosystems. Several studies have shown that allelopathic crops reduce growth, development and yield of other crops growing simultaneously or subsequently in the fields. Another aspect of interest regarding crop allelopathy is that allelochemicals may exhibit inhibitory effect on the same crop which is commonly called as crop autotoxicity. It is predominantly common in fields where sole cropping un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 250 publications
1
57
0
Order By: Relevance
“…Belowground competitive processes by which weedy plants may be outcompeted have frequently been reported in cereal-legume intercrops, and include the rapid exhaustion of existing resources (light, water and nutrients) and niches (Hauggaard-Nielsen et al 2001b;Singh et al 2003;Poggio 2005;Zarea et al 2009). In addition, allelopathic traits of certain crops have the potential to inhibit the growth of weeds (Batish et al 2001).…”
Section: Weed Suppression Via Belowground Mechanismsallelopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Belowground competitive processes by which weedy plants may be outcompeted have frequently been reported in cereal-legume intercrops, and include the rapid exhaustion of existing resources (light, water and nutrients) and niches (Hauggaard-Nielsen et al 2001b;Singh et al 2003;Poggio 2005;Zarea et al 2009). In addition, allelopathic traits of certain crops have the potential to inhibit the growth of weeds (Batish et al 2001).…”
Section: Weed Suppression Via Belowground Mechanismsallelopathymentioning
confidence: 99%
“…The list contains cultivars of common leguminous, graminaceous and brassica crop species, and species such as rye (Batish et al 2001;Fujii 2001;Bhowmik and Inderjit 2003;Singh et al 2003) and nearly 80 tree species (Rizvi et al 1999). Lemerle et al (2001) studied the effects of several wheat varieties on perennial ryegrass (Lolium perenne) and found that negative effects on the weed were partly due to environmental conditions but also due to genotype, and individual weed inhibiting traits.…”
Section: Weed Suppression Via Belowground Mechanismsallelopathymentioning
confidence: 99%
“…In such a condition suitable succeeding crop with a crop rotation has good control over it. It can limit the soil autotoxicity due to all allelopathy to a greater extend [57]. Assaduzzaman et al [58] investigated sixty seven cultivars of 42 vegetable crop species from 14 families through seedling growth bioassay using replanting soil for succeeding crops of V. faba L., P. sativum L. and P. vulgaris L. replanting soil to suggest their possible succeeding crops.…”
Section: Selection Methods Of Succeeding Crop In Replant Soilmentioning
confidence: 99%
“…In general, the chemical substances potentially involved in allelopathy are liberated from plants by leaching of foliage by rain, abscission and litter fall, volatilization and root exudation. Crop allelopathy may be useful to minimize problems affecting agricultural production such as environmental pollution, unsafe products, human health concerns, depletion of crop diversity, soil sickness and reduction of crop productivity (Batish et al, 2001). Presence of various toxic chemicals in different parts of J. curcas indicates possible allelopathic nature.…”
Section: Allelopathic Effects Of Jatropha Curcasmentioning
confidence: 99%